Analisis dan Kajian Mengenai Pertimbangan Hukum dalam Kasus Monopoli yang Terjadi di Indonesia: Studi Kasus pada Putusan KPPU Secara Mendalam - Dewi, Ratna; Agustini, Rafika Pudya; Husna, Linzy Maylika; Fathonah, Nurfitri; Wandita, Cindy Yuli; Mahuddin, Jemmy (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study analyzes the legal considerations used by the Indonesia Competition Commission (KPPU) in ruling on monopoly cases. The objective of this research is to identify the legal basis used by KPPU, analyze the impact of rulings on businesses and markets, and explore the long-term effects of KPPU’s decisions on competition in Indonesia. A qualitative approach was applied, using case studies of KPPU rulings and interviews with legal practitioners and KPPU commissioners. The findings reveal that while KPPU strives to maintain market competition, the impact on small and medium enterprises remains a significant challenge. This study recommends policies that offer more support for small and medium enterprises and adjustments in regulations to more effectively address the effects of increasing market competition.